Comparative Efficacy of DL-Methionine and Herbal Methionine on Performance of Broiler Chicken - Chattopadhyay, K.; Mondal, M.K.; Roy, B. (International Journal of Poultry Science, 2006)
An experiment was conducted to determine the comparative efficacy of DL-methionine and herbal methionine on performance and carcass characteristics of broiler chickens. Two thousand and four hundred d-old commercial broiler (VenCobb) chicks were purchased and randomly divided into four dietary treatment groups of 600 birds each. Each treatment group was further subdivided into three replicates of 200 broilers per replicate. The treatments groups were control; control plus 10g DL-methionine/kg diet; control plus 10g herbal methionine (Herbomethion®, supplied by Indian Research and Supply Co. Ltd.) /kg diet and control plus 15g herbal methionine/kg diet. There were significant effects of dietary treatments on body weight, body weight gain, feed intake and feed conversion ratio at 0 to 41 day. The body weight and body weight gain of the broilers fed the 15g herbal methionine/kg diet were heavier than other treatments. Feed conversion ratio of broiler fed 15g herbal methionine/kg diet was significantly better than that of broilers fed on 10g herbal methionine or DL-methionine/kg diet. Neither DL-methionine nor herbal methionine supplementation had a significant effect on broiler mortality. Plasma protein and enzyme concentration was unaffected by the dietary treatments. Abdominal fat (%) and liver lipid (g/kg) was significantly decreased by the addition of 15g herbal methionine/kg diet. This study demonstrates that herbal methionine can replace DL-methionine very effectively when used at the rate 15g/kg diet of commercial broiler chicken.